Sequential rTMS for MDD and OCD in a patient with left parietal perinatal ischemic infarct: a case report - Mark Odron; Vipul Reddy; Krrishika Saxena; Pailey DeBorde; Athreykrishna Parla; Charles Vigilia; Nisha Thunga; Jayleen Lu; Kenneth Blum; Rajendra D. Badgaiyan; Keerthy Sunder (Frontiers in Psychiatry, 2026)
Major depressive disorder (MDD) commonly co-occurs with obsessive-compulsive disorder (OCD), resulting in greater symptom severity, functional impairment, and suboptimal response to standard pharmacologic and psychotherapeutic interventions. These challenges underscore the need for neuromodulation strategies to target distinct neural networks implicated in mood regulation and compulsivity. This report describes outcomes of high-frequency (HF) repetitive transcranial magnetic stimulation (rTMS) of the left dorsolateral prefrontal cortex (DLPFC), and low-frequency (LF) rTMS of the right orbitofrontal cortex (OFC), in a patient with comorbid MDD, OCD, and a left parietal perinatal ischemic infarct. Over the course of treatment, serial psychometric assessments demonstrated progressive reductions in frequency and intensity of depressive symptoms, anxiety, and obsessive-compulsive behaviors, measured via Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder 7-Item Scale (GAD-7), and Yale-Brown Obsessive-Compulsive Scale (Y-BOCS). This case adds to the growing body of literature demonstrating efficacy of DLPFC and OFC stimulation for depression and OCD. Further large-scale, blinded, and randomized trials are warranted to examine the efficacy of sequential DLPFC and OFC stimulation for comorbid MDD and OCD compared with single-site DLPFC stimulation.